Developing record management instruments for Barangay Batasan Hills Office, Quezon City - Garcia, Grace A. (2018)
This project was initiated in Barangay Batasan Hills Quezon City, due to the impression that they do not have a Records Center in place. Upon inquiry it was made known that filing and recordkeeping of the documents are decentralized for having twelve (12) records creating units. It has no written policies, guidelines, or manual of procedures for the records management and no qualified or even at least trained records personnel who knows how to deal with records. With these initial findings, the Barangay Batasan Hills Office is a non-compliant to RA 9470, otherwise known as the "National Archives of the Philippines Act of 2007". Hence, a government unit who failed to comply with any of the implementing rules and regulations of RA 9470 is committing an offense that has a corresponding penalty.